What Threshold Defines Penumbral Brain Tissue in Patients with Symptomatic Anterior Circulation Intracranial Stenosis: An Exploratory Analysis. Issue 2 (6th November 2018) - Yaghi, Shadi; Khatri, Pooja; Prabhakaran, Shyam; Yeatts, Sharon D.; Cutting, Shawna; Jayaraman, Mahesh; Chang, Andrew D.; Sacchetti, Daniel; Liebeskind, David S.; Furie, Karen L.
ABSTRACT: BACKGROUND AND PURPOSE: Impaired distal perfusion predicts neurological deterioration in large artery atherosclerosis. We aim to determine the optimal threshold of T max delay on perfusion imaging that is associated with neurological deterioration in patients with symptomatic proximal anterior circulation large artery stenosis. METHODS: Data were abstracted from a prospective ischemic stroke database of consecutively enrolled patients with symptomatic proximal intracranial stenosis (internal carotid artery or M1 segment of the middle cerebral artery) who underwent magnetic resonance perfusion imaging within 24 hours of symptom onset during a 15‐month period. Tissue volumes of perfusion delay T max 0‐4 seconds, T max > 4 seconds, T max > 6 seconds, and T max > 8 seconds were calculated using an automated approach. A target mismatch (penumbra—core) was defined as ≥15mL of brain tissue using each of the T max threshold categories. The outcome was neurological deterioration at 30 days defined as new or worsening neurological deficits that are not attributed to a nonvascular etiology. RESULTS: Among 52 patients with symptomatic intracranial stenosis, 26 patients met inclusion criteria. Neurological deterioration was associated with target mismatch profile defined according to T max > 6 seconds (66.7% [6/9] vs. 5.9% [1/17], P < .01) and T max >8 seconds (57.1% [4/7] vs. 15.8% [3/19], P = .05] but not according to T max > 4 seconds (27.3% [6/17] vs. 11.1% [1/9], P = .35]. CONCLUSIONS: A target mismatch profile using T max > 6 seconds may define tissue at risk in patients with acute symptomatic proximal anterior circulation intracranial stenosis. More studies are needed to confirm our findings.